Effect of Powder Mixed Dielectric on Material Removal and Surface Modification in Microelectric Discharge Machining of Ti-6Al-4V. Issue 4 (11th March 2016) - Kuriachen, B.; Mathew, J.
Abstract : Microelectric discharge milling is one of the variants of microelectric discharge machining process which acquire the attention of researchers due to its unique ability to produce microchannels and three-dimensional structures in difficult-to-machine materials like titanium. In the present work, an experimental investigation has been performed in order to study the effect of SiC microparticle suspended dielectric on machining Ti-6Al-4V with tungsten carbide electrode. The effects of major electric discharge milling process parameters—voltage, capacitance, and powder concentration in dielectric—on responses—viz., material removal rate (MRR) and tool wear rate (TWR)—were studied. Experiments were designed and performed based on response surface methodology (RSM)-Box–Behnken statistical design and the significance of in put parameters were identified with the help of analysis of variance. From the results, it is recommended to use powder concentration of 5 g/L, capacitance of 0.1 µF, and voltage of 115 V for achieving high material removal and low tool wear rate. Finally, the studies were conducted to analyze the surface modification and the quality of machined surface.